A 30-min test applied to stand-up paddleboarding: A pilot study - Neiva, H. P.; Faíl, L. B.; Marinho, D. A. (Journal of Human Sport & Exercise, 2020)
The popularity of stand-up paddle boarding (SUP) has grown in recent decades, but little is known about SUP training and performance. The current pilot study aimed to analyse performance, biomechanical, and physiological variables during a 30-min all-out test. After a 10-min warm-up, one experienced male paddler(28years) performed a maximal 30-min SUP test wearing a Garmin Fénix 3 HR (Taipei, Taiwan) device. A total distance of 3.70 km was performed, with a mean speed of 2.19 ± 0.32 m.s-1, 52.63 ± 2.62 strokes per minute, and 2.39 ± 0.39 m per stroke. The mean heart rate (HR) was 160.78 ± 3.18 bpm, which corresponded to 85.34% (CI95%: 83.69, 85.69%) of maximal HR, and it was maintained throughout the 30-min test (coefficient of variation [CV]: 1.98%). The stroke rate was more stable throughout the test than the distance per stroke (CV: 4.98% vs. 16.20%). Significant relationships were found between speed and distance per stroke (r = -0.80, p < .001), but not between speed and stroke rate (r = 0.03, p = .75). The 30-min test was found to represent intensity of around 85% of maximal HR. The speed was negatively correlated with the distance per stroke during the test, thus suggesting that decreased distance per stroke will increase the paddling speed at constant intensities.